Can exercise attenuate the negative effects of long COVID syndrome on brain health? - Teo, Wei-Peng; Goodwill, Alicia M. (Frontiers in Immunology, 2022)
The impetus for many governments globally to treat the novel coronavirus (COVID-19) as an endemic warrant more research into the prevention, and management of long COVID syndrome (LCS). Whilst the data on LCS remains scarce, reports suggest a large proportion of recovered individuals will experience ongoing neuropsychological symptoms, even with mild disease severity. The pathophysiology underlying LCS is multifaceted. Evidence suggests that altered inflammatory, neurotrophic, and neurotransmitter pathways within the brain contribute to neuropsychological symptoms reported following COVID-19. Exercise or regular physical activity has long been shown to have positive effects on brain health and cognition through exerting positive effects on inflammatory markers, neurotransmitters, and neurotropic factors analogous to the neurophysiological pathways proposed to be disrupted by COVID-19 infection. Thus, exercise may serve as an important lifestyle behavior in the management of LCS. In this opinion article, we present the evidence to support the positive role of exercise in the management of cognitive symptom that manifest with LCS and discuss important considerations and interactions with cardiorespiratory and exercise tolerance complications that often present for individuals experiencing LCS. We highlight the need for more research and training of sports medicine practitioners and clinical exercise physiologists in the management of LCS with exercise and call for further research to understand the optimal dose-responses and exercise prescription guidelines for cognitive benefits and minimizing other complications.